Extraoral extraction of an impacted molar using bone lid technique - Göçmen, Gökhan; Varol, Altan; Basa, Selçuk; Göker, Kamil (Marmara Dental Journal, 2013)
We present a simple technique to keep the integrity of the lateral cortical wall after extraction of deeply impacted tooth located at the lower border of the mandibular base.
Keywords: Bone-lid, impacted molar, extra-oral, extraction, tooth